Peran Kebersyukuran sebagai Prediktor Psychological Well-Being pada Mahasiswa Psikologi Tahun Pertama Universitas Negeri Padang - Rodatul Jannah; Gita Syawla Indah Fitri; Rahmatul Ulfa; Hanny Rufaidah Damra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Gratitude is an important aspect and a strong foundation for creating a healthy life, both physically and mentally. Moreover, in going through the transition phase, new students certainly need aspects that can keep them physically and psychologically prosperous. This research aims to see the influence of gratitude on the psychological well-being of students who are still in their first year of study. This research method is a correlational quantitative method, with the number of subjects being 101 first year Psychology students at Padang State University. There are two measuring instruments used, namely the gratitude measuring instrument and the psychological well-being (SPWB) measuring instrument. Based on the data analysis carried out, it was found that the F value of the data was 97.787 with a significance level of 0.000 < 0.05, so that the regression model can be used to predict psychological well-being variables or in other words there is an influence of gratitude on psychological well-being. Furthermore, it is known that the R square is 0.497, meaning that 49.7% of gratitude can influence psychological well-being and 50.3% is influenced by other factors. So it can be concluded that gratitude influences the psychological well-being of first year Psychology students at Padang State University.